DESIGN AND DEVELOPMENT OF MONITORING APPLICATIONS WEB-BASED STUDENT ACTIVITIES IN AL FALAH SD ASSALAM TROPODO - Muhammad Arif Nurdiansah; Endra Rahmawati; Rudi Santoso (Jurnal Sistem Informasi Universitas Dinamika, 2018)
SD Al Falah Assalam Tropodo is the educational institutions for elementary school students in Sidoarjo city. The student attendance process is manually in the first subject and is only done once a day, so that the possibility of students not following the next subject can occur. Likewise in the extracurricular activity attendance process, there are students who use these activities to play or just spend time that is not useful. With the existence of several reports from parents of guardians who said that their children always took extracurricular activities, but in the attendance report of the school the students involved only a few times. The other problem is the lack of communication between the school and parents. During this communication only occurs when the distribution of report cards held every 3 months. As a result, parents are not getting information about the development of their children's activities. The solution given is_to_create_and design a web-based student activity monitoring application on Alfalah Assalam Tropodo Elementary School that is able to bridge parents and schools in providing information. The result of this Final Project resulted in monitoring application of student activity on SD Al Falah Assalam Tropodo. Such applications can help schools in providing real-time information to parents about their children's activities while in school.